Digital Breast Tomosynthesis Changes Management in Patients Seen at a Tertiary Care Breast Center. (3rd March 2014) - Margolies, L.; Cohen, A.; Sonnenblick, E.; Mandeli, J.; Schmidt, P. H.; Szabo, J.; Patel, N.; Hermann, G.; Weltz, C.; Port, E.
Abstract : Objectives. To study factors that predict changes in management with digital breast tomosynthesis (DBT). Methods. The Institutional Review Board approved this HIPAA compliant study. 996 patients had DBT with full field digital mammography (FFDM). Univariate analysis evaluated predictors of management change and cancer detection. Results. DBT changed management in 109 of 996 (11%); 77 (71%) required less imaging. Recalled patients after abnormal FFDM screen were most likely to have management change—25% (24 of 97 patients) compared to 8% (13/163) of symptomatic patients and 10% (72/736) of screening patients (P < 0.001 ). Dense breasted patients had a higher likelihood of having DBT change management: 13% (68/526) compared to 9% (41/470) (P = 0.03 ). Of the 996 patients, 19 (2%) were diagnosed with breast cancer. 15 cancers (83%) were seen on FFDM and DBT; 3 (17%) were diagnosed after DBT (0.3%, 95%CI: 0.1–0.9%). One recurrence was in the skin and was not seen on DBT nor was it seen on FFDM. The increase in cancer detection rate was 17% for asymptomatic patients, 0% for symptomatic patients, and 100% for recalled patients. Conclusions. DBT increased cancer detection rate by 20% and decreased the recall rate in 8–25%. Advances in Knowledge. DBT led to a doubling of the cancer detection rate in recalled patients.